Idosos com transtornos mentais em unidade fechada: percepção de profissionais da enfermagem de uma instituição de longa permanência - Costa, Adonai Mejia (2019)
It has been observed the growing need for care for the elderly with debilitating pathologies - such as mental disorders - that must be provided by a multiprofessional team. Many of these elderly people live in long-term care facilities for the elderly (ILPI) and are assisted in closed units. The objective of the study was to describe the perception of nursing professionals of a LTIPI about the presence of a closed unit in which elderly people with mental disorders reside and to describe how nursing professionals provide care for the elderly with mental disorders residing in a closed an ILPI. The research was carried out in an ILPI, located in the southern region of Brazil. To collect the data, the technique of creativity and sensitivity (TCS) and semi-structured interview with 15 nursing professionals of the institution were used. The ethical aspects of human research have been respected. The data were analyzed following the steps of the thematic analysis. The results, about the perception of the nursing professionals about the closed unit of the ILPI, demonstrate the precariousness of the physical structure of this place, understanding it as a place of exclusion, sad, with lack of activities, but necessary to guarantee safety and protection of the elderly. Regarding nursing care provided to the elderly with mental disorder in the closed unit, the participants reported difficulties in providing care due to fear, fear and insecurity when assisting elderly women with mental disorder. There was also mention that caring for the elderly in the closed unit was quiet. It is considered that this work can contribute to know the reality of the work of nursing professionals in a closed unit of an ILPI, which assists elderly women with mental disorder. In addition, it points out its difficulties and strategies to "survive" in this environment - even if it seeks to offer qualified care.